From maize to tlayuda, a traditional big-flat leathery tortilla. Effect of two nixtamalization processes on some physicochemical and nutraceutical properties - Vazquez-Carrillo, Maria Gricelda; Toledo-Aguilar, Rocio; Aragon-Cuevas, Flavio; Salinas-Moreno, Yolada; Palacios-Rojas, Natalia; Santiago-Ramos, David (Elsevier, 2023)
Tlayudas are a kind of native-traditional tortillas gaining popularity around the world. This study addresses the effect of two nixtamalization methods (traditional and artisanal) on some physicochemical and nutraceutical properties of tlayudas made from three native and five improved maize ‘Bolita’ landrace samples. Two commercial hybrids were used as controls. All native and improved samples showed grains with higher test weight (>77 kg hL−1) and bigger size grains compared to those hybrids normally used for table tortilla production. Artisanal nixtamalization involved a higher concentration of lime (3.0 %w/w) and a more exhaustive rinsing leading that more of the hydrolyzed pericarp being lost in the cooking solution and the rinsing water. A lower retained pericarp was associated with a softer masa and a less leathery tlayuda texture. Tlayudas made from blue maize had significantly (p < 0.05) higher content of phenolics and the highest antioxidant capacity (DPPH and ABTS methods), which was around 4.5-fold higher than that of yellow maize tlayudas. HPLC results indicated the acylated and non-acylated cyanidins, mainly cyanidin-3-glucoside, which increased after processing due to the degradation of the acylated cyanidins. Yellow tlayudas showed better retention of phenolics and carotenoids compounds, mainly Provitamin A carotenoids. This study showed that the nixtamalization process did not greatly impact the nutraceutical properties of tlayudas, these properties are more dependent on the type of maize.